Endoscopist-Directed Propofol as an Adjunct to Standard Sedation: A Canadian Experience - Heron, Valérie (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Sedation practices vary widely by region. In Canada, endoscopist-directed administration of a combination of fentanyl and midazolam is standard practice. A minority of cases are performed with propofol. AIMS: To describe the safety of nonanaesthetist administered low-dose propofol as an adjunct to standard sedation. METHODS: This was a single-centre retrospective study of patients having undergone endoscopic procedures with propofol sedation between 2004 and 2012 in a teaching hospital in Montreal. Procedures were performed by gastroenterologists trained in Advanced Cardiovascular Life Support. Sedation was administered by intravenous bolus by a registered nurse, under the direction of the endoscopist. Outcomes of procedures were collected in the context of a retrospective chart review using the hospital’s endoscopy database. RESULTS: Of patients undergoing endoscopies at our centre, 4930 patients received propofol as an adjunct to standard sedation with fentanyl and midazolam. Cecal intubation rate for colonoscopies (n = 2921) was 92.0%. Gastroscopies (n = 1614), flexible sigmoidoscopies (n = 28), endoscopic retrograde cholangiopancreatography (n = 331) and percutaneous endoscopic gastrostomy insertion (n = 36) had success rates, defined as successful completion of the procedure within anatomical limits, of 99.0, 96.4, 94.0 and 91.7%, respectively. The average dose of propofol used for each procedure was 34.5 ± 20.8 mg. Fentanyl was used in 67.4% of procedures at an average dose of 94.3 ± 17.5 mcg. Midazolam was used in 92.7% of cases at an average dose of 3.0 ± 0.7 mg. Reversal agents (naloxone or flumazenil) were used in 0.43% of the cases (n = 21). Patients who received propofol were discharged uneventfully within the usual postprocedure recovery time. One patient required sedation-related hospitalization. For patients having received propofol in addition to standard sedation agents, 99.6% experienced no adverse events. There were no mortalities. CONCLUSION: The use of low-dose propofol as an adjunct to fentanyl and midazolam, administered by a registered nurse under the direction of the endoscopist was safe and effective in patients at our centre.